1984
DOI: 10.1055/s-2008-1044160
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Successfully Operated Oesophageal Atresia - With Aspects on Physical and Psychological Development

Abstract: From 1966 to 1973, 43 oesophageal atresia patients with no other significant anomalies underwent successful anastomosis. The late mortalities of the 5 patients were due to the complications of gastro-oesophageal reflux and tracheal problems. These deaths and all the serious complications occurred before the age of 3 years. The survivors were followed up for a mean of 12.7 years and 34 of the 38 long-term survivors were re-examined by the author. The subjective results of the remaining 4 patients were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In contrast, in two cross-sectional studies from different centres in Finland normal physical growth was reported in children with a mean age of 12 years studied several decades ago (7,9), and Legrand and coworkers recently even found overweight/obesity in 9% of 57 type C OA-patients studied at a mean age of 13 years(10).…”
Section: Physical Growthmentioning
confidence: 75%
See 2 more Smart Citations
“…In contrast, in two cross-sectional studies from different centres in Finland normal physical growth was reported in children with a mean age of 12 years studied several decades ago (7,9), and Legrand and coworkers recently even found overweight/obesity in 9% of 57 type C OA-patients studied at a mean age of 13 years(10).…”
Section: Physical Growthmentioning
confidence: 75%
“…Only three cross-sectional studies on cognition in OA-patients at school age are available (7,25,26). In 1984, Lindahl reported normal intelligence at an age of 8.8 to 16.5 years (mean age 12.7 years) in a cohort of 33 OA-patients born between 1966 and 1973.…”
Section: Neurodevelopmental Outcomementioning
confidence: 98%
See 1 more Smart Citation
“…Lindahl et al [34] reported IQ in the normal range in children with EA. The results are probably dependant on the presence of associated congenital malformation and prematurity.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the challenges child and parents experience in the early years, most adult patients with EA seem to have a good quality of life [15,16]. There is a paucity of studies that have examined long-term psychological outcome of children with EA; and the results reporting psychosocial functioning are contradictory, ranging from comparable with those of healthy controls [11,15,17,18] to more emotional and learning problems [19,20]. Because these studies have few patients in each age group and different assessment procedures have been used, it is difficult to make any firm conclusions.…”
mentioning
confidence: 98%